2006
DOI: 10.1590/s0103-50532006000500011
|View full text |Cite
|
Sign up to set email alerts
|

Gaseous and particulate atmospheric mercury concentrations in the Campinas Metropolitan Region (São Paulo State, Brazil)

Abstract: As concentrações de Mercúrio Gasoso Total (MGT) e Mercúrio Particulado Total (MPT) foram monitoradas durante as estações seca e úmida de 2002-2003 em dois pontos (industrial e residencial) da Região Metropolitana de Campinas. Não foi observada diferença significativa entre as concentrações dos pontos de amostragem e as concentrações médias foram 7,0 ± 5,8 ng m -3 (MGT) e 0,4 ± 0,3 ng m -3 (MPT). A análise da variação nictemeral mostrou maior concentração de MGT durante o dia, que poderia estar relacionada com … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 20 publications
0
7
1
1
Order By: Relevance
“…There were only a few, mostly short-term, measurements of mercury species in the urban atmosphere. [11][12][13][14][15] The results from these studies showed higher levels of mercury species in the urban atmosphere than in rural and non-urban airsheds, suggesting anthropogenic sources of mercury in urban areas. 11,15 When urban sites with and without impacts from industrial activities were compared, there was no significant difference in the concentrations of atmospheric mercury species between the two sites, 12 and the values are much higher than those observed in a rural area.…”
Section: Introductionmentioning
confidence: 72%
“…There were only a few, mostly short-term, measurements of mercury species in the urban atmosphere. [11][12][13][14][15] The results from these studies showed higher levels of mercury species in the urban atmosphere than in rural and non-urban airsheds, suggesting anthropogenic sources of mercury in urban areas. 11,15 When urban sites with and without impacts from industrial activities were compared, there was no significant difference in the concentrations of atmospheric mercury species between the two sites, 12 and the values are much higher than those observed in a rural area.…”
Section: Introductionmentioning
confidence: 72%
“…Higueras et al (2005) observed very high TGM concentrations near historical mining regions along roads in the Coquimbo region of Northern Chile, reaching extremely high TGM values, up to 100 µg m −3 at some gold recovery operations (milling and amalgamation). Fostier and Michelazzo (2006) performed TGM measurements at two sites in Sao Paulo State, Brazil, near an industrial area. An average TGM concentration of 7.0 ng m −3 was observed at both sites.…”
Section: Mercury Measurements In South America and Mexicomentioning
confidence: 99%
“…The concentrations of PHg measured in this study range from 6.5 to 29.3 pg m À3 , which are in the same range as those reported in the literature for total particulate mercury in suburban areas. 9,18 In Brazil, the only PHg concentrations were reported by Fostier and Michelazzo, 19 who found 465 AE 252 pg m À3 at Unicamp. Nevertheless, in this study, air sampling was performed at 2 m, which could have signicantly increased the PHg concentration because of the soil dust inuence.…”
Section: Resultsmentioning
confidence: 96%